Ultra-fast spectroscopy investigation of Verwey transition in magnetite - A Mokhtari (Iranian Journal of Physics Research, 2015)
Magnetite has a different electrical resistance behavior with temperatures below and above the Verwey temperature. Here, we report on Verwey transition in Fe3O4 by means of the frequency-doubled output from the Ti-sapphire laser in pump-probe experiments and from the insulator to metal transition observed by changing the temperature at the wavelength 370nm (~3.36 eV) both for pump and probe. We observed a clear difference below and above the Verwey temperature in ultra-fast transmission changes.